Effects of lead contamination on the clonal propagative ability of Phragmites australis (common reed) grown in wet and dry environments. (9th April 2015) - Zhang, N.; Zhang, J. W.; Yang, Y. H.; Li, X. Y.; Lin, J. X.; Li, Z. L.; Cheng, L. Y.; Wang, J. F.; Mu, C. S.; Wang, A. X.; Luo, Z.‐B.
Abstract Clonal propagation is important for the survival and maintenance of the common reed Phragmites australis. Pot culture experiments were conducted to investigate the effects of lead (Pb) concentration (0, 500, 1500, 3000, 4500 mg·kg−1) and water stress on the clonal reproductive ability of this species. The Pb concentration found in plant organs, in decreasing order, was roots >shoots >rhizomes. There was a negative relationship between the growth of clonal propagative modules (excluding axillary shoot buds) and Pb concentrations, which caused a decrease in biomass, rhizome growth and number of axillary and apical rhizome buds. Daughter axillary shoots exhibited a tolerance strategy, with no significant change in their number; the axillary and apical rhizome buds, daughter apical rhizome shoots and rhizomes exhibited compensatory growth during the late stage of Pb (excluding 4500 mg·kg−1) treatment in a wet environment. Pb applications above 500 mg·kg−1 reduced these parameters significantly in the drought treatment, except for the number of axillary shoot buds, which did not change. Our results indicate that clonal propagative resistance to Pb contamination can occur via tolerance strategies, compensatory growth and a Pb allocation strategy, enabling these reeds to maintain population stability in wet environments. However, clonal modular growth and reproductive ability were inhibited significantly by the interaction between drought and Pb, which would cause a decline in P. australis populations in a dry environment. Lead concentrations of 4500 and 500 mg·kg−1 in soils might meet or exceed the Pb tolerance threshold of clonally propagated reeds in wet and dry environments, respectively.